Black Students on the Yard and on the Quad: Education Degrees at HBCUs and Non-HBCUs. (3rd July 2022) - Houston, Derek A.; Cormier, Christopher J.; Petchauer, Emery; Scott, LaRon A.
Abstract: Analyzing degree attainment data over a 30-year period, the authors found that relative to their enrollment, HBCUs overproduce Black graduates who obtain education degrees compared to non-HBCUs. Furthermore, Black men receiving education degrees at HBCUs do so at higher rates than their overall enrollment. Implications for school districts, teacher education programs, and policy are provided.